A many‐splendored thing? Transformative learning for social justice. Issue 177 (14th February 2023) - Finnegan, Fergal
Abstract: This article critically reviews literature dealing with transformative learning and social justice. Based on a review of literature from major journals and conference proceedings concerned with transformative learning it offers an assessment of the significance of social justice research in the wider field. It describes how social justice is envisaged and approached theoretically, methodologically, and thematically in the reviewed publications. The article also critically assesses the strengths and limitations of research on this topic and offers some suggestions on how research on this topic might be advanced in the future.